2012
DOI: 10.1111/j.1442-200x.2012.03563.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of the major skin microbiota, Malassezia, from mother to neonate

Abstract: Fungal microbiota colonization of neonates began on day 0, and the fungal microbiota of neonates had changed to the adult type by day 30. To our knowledge, this is the first report of a molecular analysis of the fungal microbiota of neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 21 publications
3
60
2
Order By: Relevance
“…While cutaneous mycobiome investigations of healthy Asian individuals based in Japan [3, 4, 22, 5456], Korea [5], and India [57] have been conducted, investigations on Chinese individuals have been limited to prokaryote communities [12, 52, 58]. By selecting only Chinese subjects in our study, our cohort is a representative model of the Chinese population in HK, and while subjects in this study may not represent other Chinese individuals [58], this study is nonetheless fundamental in beginning to understand the skin mycobiome of the Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…While cutaneous mycobiome investigations of healthy Asian individuals based in Japan [3, 4, 22, 5456], Korea [5], and India [57] have been conducted, investigations on Chinese individuals have been limited to prokaryote communities [12, 52, 58]. By selecting only Chinese subjects in our study, our cohort is a representative model of the Chinese population in HK, and while subjects in this study may not represent other Chinese individuals [58], this study is nonetheless fundamental in beginning to understand the skin mycobiome of the Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…The skin mycobiome, for example, is thought to change drastically early in life. Using the genotyping of Malassezia species as an indicator, one study demonstrated that it takes 30 days for the skin microbiota to change from its initial state to an adult type [44]. …”
Section: Composition and Role Of The Mycobiome In Health And Diseasementioning
confidence: 99%
“…Interestingly, it has also been shown that the common fungal commensal Malassezia colonizes neonate skin during the birthing process [46]. At day 0 following delivery, Malassezia DNA was successfully detected in 24 of 27 subjects, and by day 30 approximately 10 4 residents were estimated by qPCR.…”
Section: Host Factors and The Skin Microbiotamentioning
confidence: 99%